Development of a promotion based on a study of consumer preferences in the beer market - Suchkov Aleksandr (2019)
For my thesis work, I wanted to choose a topic that can be connected to my studying direction and which can cover many topics of marketing and management. First I will analyze the theoretical background of promotion development. I will find out which types of analyses exists, how we should prepare for marketing campaigns, niche researches and which tools we can use. I decided to choose a beer market in Russia because it is a huge market and it is not the same as any other. In Russia, all alcohol production advertisement is strictly controlled by the government. It will be very interesting to see how companies can promote their products in limited conditions. Usually, on markets like beer, there are many brands but most of them are very old and big. We will analyze what new players need to do to enter the market and if it is even possible at all for a new product to launch under current circumstances. In purpose to make correct decisions and conclusions I will prepare qualitative and quantitative analyses. To get actual data qualitative analysis will be done among 800 people, different ages, interests, profits and in different regions of the city. Quantitative analyses will be done using the focus group method with the chosen category of people and well-prepared questions. After all, data was collected I need to carefully analyze it. Every question had to be described and results need to be interpreted accordingly. Also, I did a couple of cross analyses with connected questions. As a result of full work, I got a clear picture of the current market which was described in the conclusion. I found leaders and looser of the markets, their strong and weak parts. Also, I described possible options and ways for promotion alcohol product, marketing and merchandising even in very limited conditions.